The Toronto Blessing and slaying in the Spirit the telling wonder; a compelling new approach to the Pentecostal Charismatic signs and wonders debate - Mikhaiel, Nader (Earlwood, NSW Nader Mikhaiel, 1992)
Includes bibliographical references.
Keywords: Charismatic movement -- controversial literature; Gifts, spiritual -- biblical teaching; Toronto blessing